Non-contact subsurface thermography for high-temperature metallic structures using laser ultrasound and wave-equation-based inversion - Hu, Lei (2023)
Temperature distribution is an important factor influencing the formation of defects in engineering components operating at high temperatures. A non-contact thermographic method based on the laser-ultrasonic technique and the wave-equation-based inversion (WEBI) algorithms is proposed. Three algorithms, which are full waveform inversion (FWI), traveltime waveform inversion (TWI), and double-difference traveltime waveform inversion (DDTWI), are used to reconstruct the temperature maps of the subsurface region of high-temperature metals. The performances of the algorithms are investigated both numerically and experimentally. Among these algorithms, FWI shows the highest accuracy and the largest reconstruction depth but is also susceptible to noise. TWI and DDTWI show similar performances in terms of the reconstruction depth and accuracy, while TWI has better resistance to noise.